Epidemiological characteristics of influenza-like illness outbreaks in long-term care facilities of the state of São Paulo, Brazil - Pamella Cristina de Carvalho Lucas; Yeda Aparecida de Oliveira Duarte; Eliana Tiemi Masuda; Camila Martins Trevisan; Raquel Gardini Sanches Palasio; Patrícia Marques Ferreira; Ana Lucia Frugis Yu; Telma Regina Marques Pinto Carvalhanas (Brazilian Society of Geriatrics and Gerontology, 2021)
Long-term care facilities for older adults present a high risk of outbreaks since they concentrate often more frail and vulnerable individuals. OBJECTIVE: To describe the epidemiological characteristics of influenza-like illness outbreaks and cases among older people in long-term care facilities in the state of São Paulo, Brazil. METODS: The analysis was performed through an exploratory and descriptive approach, with records from the outbreak module of the National System of Notifiable Diseases between January 2020 and June 2021. RESULTS: Outbreaks of influenza-like illness in this department represented 24.93% of all notifications. The highest concentration was seen in the state capital and metropolitan area. A total of 1 018 confirmed outbreaks were observed, involving 6 110 cases and 1 240 deaths among older people. Of these cases, 71.67% were confirmed for coronavirus disease 19 (COVID-19), 12.77% for the influenza virus, and 15.56% for other respiratory viruses. The percentages regarding death outcomes were similar, with a 20.29% lethality of influenza-like illness. Within the studied group, the older adults were the most affected. A statistical difference was observed between cases and deaths. CONCLUSIONS: Owing to the current scenario and the known vulnerabilities of these facilities, there is an urgent need for joint and articulated action by various administrative levels in order to minimize the devastating effects of influenza-like illness outbreaks (especially of COVID- 19) in older adults at long-term care homes. The strengthening of information systems and their interoperability are considered of utmost importance in order to improve the quality of information on outbreaks, which is essential during a pandemic.